Exploring Indigenization and decolonization in cross-cultural education through collaborative land-based boundary education. Issue 1 (2nd January 2022) - Zurba, Melanie; Land, George; Bullock, Ryan; Graham, Bridget
ABSTRACT: This article considers the potential for collaboratively produced boundary education as an advancement of the boundary work concept in academia. The boundary work process aims to support collaboration that works around social, cultural, political, epistemological, and other forms of boundaries. We explore how education can act as a boundary object through the development and implementation of a pilot project for land-based educational programming offered through a university. In particular, we share observations arising through a land-based education initiative that engaged Indigenous land stewards from Wabaseemoong Independent Nation and students from The University of Winnipeg. Our approach is grounded in an extended conceptual framework and process for conducting boundary work in the context of collaborative educational design and implementation involving educators from academia and Indigenous community partners. The pilot project provided baseline insights for future boundary education collaborations and provided some direction for future work.